Changes in the growth and physiological property of tea tree after aviation mutagenesis and screening and functional verification of its characteristic hormones - Jia, Miao; Chen, Yiling; Zhang, Qi; Wang, Yuhua; Li, Mingzhe; Pang, Xiaomin; Hong, Lei; Lin, Shaoxiong; Jia, Xiaoli; Ye, Jianghua; Wang, Haibin (Frontiers in Plant Science, 2024)
Aerospace breeding is a breeding technique that utilizes spacecraft to place plants in a space environment for mutagenesis, which is conducive to rapid mutagenesis to screen for superior plant varieties. In this study, tea trees with aviation mutagenesis (TM) and without aviation mutagenesis (CK) were taken as research objects to analyze the effects of aviation mutagenesis on the growth, physiological property and hormone metabolism of tea trees, to screen the characteristic hormones and carry out functional validation. The results showed that the leaf length, leaf width and leaf area of TM tea trees were significantly larger than those of CK. Growth indexes, photosynthetic physiological indexes (chlorophyll content, intercellular CO2 concentration, stomatal conductance, transpiration rate and photosynthetic rate) and resistance physiological indexes (superoxide dismutase, peroxidase, catalase and soluble sugar) were significantly higher in TM than in CK. Hormone metabolome analysis showed that four characteristic hormones distinguished CK from TM, i.e., L-tryptophan, indole, salicylic acid, and salicylic acid 2-O-β-glucoside, all of which were significantly more abundant in TM than in CK. The four characteristic hormones were significantly and positively correlated with the growth indexes, tea yield, photosynthetic physiological indexes and resistance physiological indexes of tea trees. The leaf area, chlorophyll content, photosynthetic rate and superoxide dismutase activity of tea tree seedlings after spraying with the four characteristic hormones were significantly increased, in which salicylic acid, salicylic acid 2-O-β- glucoside were more favorable to increase leaf area and superoxide dismutase activity, while L-tryptophan, indole were more favorable to increase leaf chlorophyll content and photosynthetic rate. It can be seen that aviation mutagenesis improves the accumulation of characteristic hormones of tea trees, enhances the photosynthetic capacity of tea trees, improves the resistance of tea trees, promotes the growth of tea trees, and then improves tea yield.